Effectiveness of Paired Reading Strategy on Reading Ability of Struggling Readers in Primary Schools in Uyo L.G.A, Akwa Ibom State - Olaoluwa, Olota Philip; Ebey, Samitha (American Journal of Creative Education, 2022)
The study examined the effectiveness of paired reading strategy on reading ability of struggling readers in Uyo Local Government Area, Akwa Ibom State, Nigeria. A quasi-experimental study was adopted. The study population was all the 2,974 primary three pupils in all the 47 public primary schools. The purposive sampling technique was used to select a sample size of 73 primary three pupils from two intact classes. Reading Level Classificatory Test (RLCT) (Beginners), Reading Level Classificatory Test (RLCT) (Intermediate), Reading Level Classificatory Test (RLCT) (Proficient) and Struggling Readers Reading Ability Test (SRRAT) were used as the instruments for the study.. Kudar Richardson Formula 21 was used to determine the internal consistency of the instruments, which yielded coefficient indexes of 0.68 for Reading Level Classificatory Test (Beginners), 0.74 for intermediate, 0.69 for proficient and 0.90 for SRRAT. Mean and standard deviation were used to answer the research questions while analysis of covariance (ANCOVA) was used to test the hypothesis. The study revealed a significant difference in the mean reading ability scores of struggling readers exposed to paired reading strategy and those exposed to choral reading strategy. Based on the study's findings, the researchers recommended, among others, that all classroom teachers make efforts to integrate paired reading strategy into teaching reading.